2017
DOI: 10.1016/j.neuron.2017.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Cell-Type-Specific Olfactory Processing in the Drosophila Mushroom Body Circuit

Abstract: How cell-type-specific physiological properties shape neuronal functions in a circuit remains poorly understood. We addressed this issue in the Drosophila mushroom body (MB), a higher olfactory circuit, where neurons belonging to distinct glomeruli in the antennal lobe feed excitation to three types of intrinsic neurons, α/β, α'/β', and γ Kenyon cells (KCs). Two-photon optogenetics and intracellular recording revealed that whereas glomerular inputs add similarly in all KCs, spikes were generated most readily i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 70 publications
9
59
0
Order By: Relevance
“…that predicts that the average Kenyon cell inhibits itself more than it inhibits other 532 individual Kenyon cells. This prediction is supported by previous experimental results 533 that some Kenyon cells can inhibit some Kenyon cells more than others, and that an 534 individual Kenyon cell can inhibit itself (Inada et al, 2017). Our model goes beyond 535 these results in predicting that the average Kenyon cell actually preferentially inhibits 536 itself ( Fig.…”
Section: Apl Inhibit Kenyon Cells Where It Itself Is Not Active? Widesupporting
confidence: 76%
See 1 more Smart Citation
“…that predicts that the average Kenyon cell inhibits itself more than it inhibits other 532 individual Kenyon cells. This prediction is supported by previous experimental results 533 that some Kenyon cells can inhibit some Kenyon cells more than others, and that an 534 individual Kenyon cell can inhibit itself (Inada et al, 2017). Our model goes beyond 535 these results in predicting that the average Kenyon cell actually preferentially inhibits 536 itself ( Fig.…”
Section: Apl Inhibit Kenyon Cells Where It Itself Is Not Active? Widesupporting
confidence: 76%
“…We first asked whether physiological responses to sensory stimuli are spatially 97 localized within APL. At very low odor concentrations, odor responses in APL can be 98 restricted to one lobe (Inada et al, 2017), but it remains unclear how sensory-evoked 99 activity is structured across APL at larger scales. We examined this question using 100 electric shock, a typical 'punishment' used for olfactory aversive conditioning.…”
mentioning
confidence: 99%
“…To understand this issue, it would necessary to identify the basic components of the decoder: (i) convergence of input from multiple PNs onto downstream neurons, (ii) linear combination of the inputs, and (iii) a detection threshold that does not require all input neurons to be simultaneously co-active. Existing anatomical and functional studies have shown that downstream Kenyon cells in the mushroom body linearly combine inputs from multiple projection neurons 43,44 . Further photostimulation of Kenyon cell dendritic claws in fruit flies have revealed that activating more than half of these input regions is sufficient for driving these cells to spike 45 (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Second, lateral inhibition mediated by the LNs in the AL (Wilson, 2013) facilitates decorrelation of odor representations (Wilson and Laurent, 2005;Schmuker et al, 2011;Wilson, 2013;Campbell et al, 2013) and contributes to population sparseness (Luo et al, 2010;Betkiewicz et al, 2020). The sparse code in the KC population has been shown to reduce the overlap between different odor representations (Luo et al, 2010;Lin et al, 2014;Inada et al, 2017) and consequently population sparseness is an important property of olfactory learning and plasticity models in insects (Huerta et al, 2004;Huerta and Nowotny, 2009;Wessnitzer et al, 2012;Ardin et al, 2016;Peng and Chittka, 2017;Müller et al, 2018).…”
Section: Sparse Coding In Space and Timementioning
confidence: 99%
“…(Aso et al, 2014a;Caron et al, 2013;Xu et al, 2020)) and neurophysiology (e.g. (Ito et al, 2008;Kazama and Wilson, 2009;Demmer and Kloppenburg, 2009;Szyszka et al, 2014;Inada et al, 2017;Egea-Weiss et al, 2018)) of insect olfaction and basic computational features (Litwin-Kumar et al, 2017;Kloppenburg and Nawrot, 2014;Betkiewicz et al, 2020). We follow the idea of compositionality, a widely used concept in mathematics, semantics and linguistics.…”
mentioning
confidence: 99%